Judicial control as a guarantee of non-interference in private life during the pre-trial investigation: An observation under the European Court of Human Rights - Galagan, Volodymyr I.; Ablamskyi, Serhii Ye.; Udovenko Zhаnnа V.; Ablamska, Victoria V. (DIXI, 2021)
The article is devoted to the topical issue of judicial control over non-interference in the private (personal and family) life of participants in criminal proceedings. The study was conducted in the context of the analysis of the practice of the European Court of Human Rights, the legal positions of which should be consistently applied in criminal proceedings; evidence of this are the legal requirements on this issue. The notion and concept of judicial control is a necessity component that helps to guarantee the respect of human dignity and integrity. It is a common and established principle that, during the pre-trial process, it is the position of those ensuring justice in making sure that the life of people is respected and safeguarded. It is noted that in accordance with the national legislation of Ukraine, judicial control is a separate function of the court’s activities at the stage of pre-trial investigation, directly carried out by the investigating judge. The situation will become precarious and detrimental when the private life of people is not respected to the fullest. Therefore, it is the responsibility of those ensuring public order during the pre-trial investigation phase to ensu-re the respect of the private life of the presumed suspect for the proper implementation of the justice process. In ensuring this right, it is established that the empirical and analytical methods of research are necessary, in order to show the effective role played by the European Court of Human Rights in respecting the right to private life during the interrogative phase of inquiry. From the findings, it is seen that, though the Court has played a prominent and pertinent role in the respect of private life, the suspect continues experiencing difficulties when his/her private life is at stake, and it always affects the extent of the justice system.